Properties of hadronic final states in diffractive deep inelastic ep scattering at DESY HERA - Chekanov, S; Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Pellegrino, A; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Basile, M; et al. (2002)
Characteristics of the hadronic final state of diffractive deep inelastic scattering events ep→eXp were studied in the kinematic range 4